Cultural politics and education - Apple, Michael W. (Buckingham : Open University Press, 1996)
Education, identity, and cheap French fries. The politics of official knowledge: does a national curriculum make sense? Becoming right: education and the formation of conservative movements with Anita Oliver. American realities. Conclusion.
Keywords: Education; United States; Political aspects; Education -- Political aspects -- United States; Critical pedagogy -- United States; Education -- Social aspects -- United States